The frequency and chemical phenotype of neighboring plants determine the effects of intraspecific plant diversity - Andrea E. Glassmire; Kayleigh C. Hauri; Daniel B. Turner; Luke N. Zehr; Koichi Sugimoto; Gregg A. Howe; William C. Wetzel (Ecology, 2024)
Associational effects, whereby plants influence the biotic interactions of their neighbors, are an important component of plant–insect interactions. Plant chemistry has been hypothesized to mediate these interactions. The role of chemistry in associational effects, however, has been unclear in part because the diversity of plant chemistry makes it difficult to tease apart the importance and roles of particular classes of compounds. We examined the chemical ecology of associational effects using backcross‐bred plants of the Solanum pennellii introgression lines. We used eight genotypes from the introgression line system to establish 14 unique neighborhood treatments that maximized differences in acyl sugars, proteinase inhibitor, and terpene chemical diversity. We found that the chemical traits of the neighboring plant, rather than simply the number of introgression lines within a neighborhood, influenced insect abundance on focal plants. Furthermore, within‐chemical class diversity had contrasting effects on herbivore and predator abundances, and depended on the frequency of neighboring plant chemotypes. Notably, we found insect mobility—flying versus crawling—played a key role in insect response to phytochemistry. We highlight that the frequency and chemical phenotype of plant neighbors underlie associational effects and suggest this may be an important mechanism in maintaining intraspecific phytochemical variation within plant populations.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic analysis of the tomato inquieta mutant links the ARP2/3 complex to trichome development - Na-Rae Jeong; Heejin Kim; In-Taek Hwang; Gregg A. Howe; Jin-Ho Kang (Journal of Plant Biology, 2017)

Jasmonate-Triggered Plant Immunity - Marcelo L. Campos; Jin-Ho Kang; Gregg A. Howe (Journal of Chemical Ecology, 2014)

Jasmonates as signals in the wound response - Gregg A. Howe (Journal of Plant Growth Regulation, 2004)

Jasmonates as Signals in the Wound Response - Gregg A. Howe (Journal of Plant Growth Regulation, 2004)

Alternative splicing of prosystemin pre-mRNA produces two isoforms that are active as signals in the wound response pathway - Lei Li; Gregg A. Howe (Plant Molecular Biology, 2001)